Non-pharmacological sleep interventions for pediatric cancer patients and survivors: a systematic review protocol - Peter L. Stavinoha; Ineke M. Olsthoorn; Maria C. Swartz; Sara Nowakowski; Stephanie J. Wells; Rachel S. Hicklen; Irtiza Sheikh; Hannah J. Jang (Systematic Reviews, 2021)
Abstract Background Sleep disturbances constitute a common complication in pediatric cancer patients and survivors and are frequently severe enough to warrant treatment. Suboptimal sleep has been associated with decreased emotional well-being and cognitive functioning and increased behavioral problems. Standardized guidelines for non-pharmacological sleep interventions for adults with cancer exist, but no standard of care intervention or standard guidelines are available to guide such intervention in pediatric cancer patients and survivors. Therefore, effective behavioral interventions for improving sleep quality need to be identified. The objective of the review is to evaluate the effect of non-pharmacological sleep interventions on sleep quality in pediatric cancer patients and survivors. Methods The review will consider studies that include children and adolescents between 0 and 18 years diagnosed with cancer or who have a history of cancer who have non-respiratory sleep disturbance. We will include experimental and quasi-experimental studies evaluating non-pharmacological interventions such as psychological interventions, technical/device interventions, interventions targeting physical activity, and complementary and alternative medicine interventions (e.g., yoga, massage, music). Interventions involving medications, ingestible supplements, products purported to work through absorption, and medical devices will be excluded. Primary outcome will be sleep quality as measured by methods including retrospective ratings, daily sleep diary, and validated questionnaires. Secondary outcomes will include total sleep time, sleep onset latency, wake after sleep onset, daytime sleepiness, and daytime sleep duration (naps) as measured by retrospective ratings, daily sleep diary, validated questionnaires, and/or actigraphy. Databases will include MEDLINE (Ovid), EMBASE (Ovid), Cochrane Library, CINAHL (Ebsco), and PsycINFO (Ovid) and will be queried from database inception to present. Two reviewers will independently screen all citations, full-text articles, and extract data. The study methodological quality will be assessed using Joanna Briggs Institute (JBI) critical appraisal tools. Data will be extracted and findings pooled and synthesized using a meta-aggregation approach via the JBI System for the Unified Management, Assessment, and Review of Information (SUMARI). If feasible, we will conduct random effects meta-analysis. Additional analyses will be conducted to explore the potential sources of heterogeneity (e.g., methodological quality, study design, outcome measures). Discussion This systematic review will synthesize and consolidate evidence on existing non-pharmacological interventions to improve sleep in pediatric cancer patients and survivors. Findings may help inform practitioners working with pediatric cancer patients and survivors experiencing sleep disturbances and is intended to identify gaps and opportunities to improve methodical quality of further non-pharmacological sleep intervention research in this population toward developing an eventual standard of care. Systematic review registration PROSPERO CRD42020200397 .